The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3390/cryst2041382
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fiber for High-Power Optical Communication

Abstract: Abstract:We examined optical fibers suitable for avoiding such problems as the fiber fuse phenomenon and failures at bends with a high power input. We found that the threshold power for fiber fuse propagation in photonic crystal fiber (PCF) and hole-assisted fiber (HAF) can exceed 18 W, which is more than 10 times that in conventional single-mode fiber (SMF). We considered this high threshold power in PCF and HAF to be caused by a jet of high temperature fluid penetrating the air holes. We showed examples of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…When 2R In is much larger than D melted , the fiber fuse propagates in the same way as in SMF. However, no fiber fuse propagates even at an input power of 18.0 W, when 2R In is much smaller than D melted [51,56]. Figure 19A shows a side view of a splice point between an SMF and HAF-A before and after fiber fuse propagation at a wavelength of 1480 nm.…”
Section: Propagation Characteristics Of Fiber Fuse In Hafmentioning
confidence: 99%
See 1 more Smart Citation
“…When 2R In is much larger than D melted , the fiber fuse propagates in the same way as in SMF. However, no fiber fuse propagates even at an input power of 18.0 W, when 2R In is much smaller than D melted [51,56]. Figure 19A shows a side view of a splice point between an SMF and HAF-A before and after fiber fuse propagation at a wavelength of 1480 nm.…”
Section: Propagation Characteristics Of Fiber Fuse In Hafmentioning
confidence: 99%
“…Furthermore, HAF has a great advantage with a view to avoiding failures at bends under high power [35], because HAF is a low-bending-loss optical fiber [19]. Therefore, we consider HAF to be an attractive optical fiber as a solution for the problems posed by the fiber fuse phenomenon and failures at bends with a high power input [56].…”
Section: Compact Fiber Fuse Terminator Consisting Of Hafmentioning
confidence: 99%
“…They considered that the plasma density of the core decreased in connection with the disappearance of the hole part and that the propagation of a fiber fuse can be controlled even if a high power of 10 W order is input into an HAF. In practice, they observed the dynamics of fiber fuse termination near the splice point between HAF2 and the SMF and found that the termination was accompanied by the evolution of a gas jet in the case of P 0 = 12 W [48] and 18.1 W (6.6 W at 1.48 µm and 11.5 W at 1.55 µm) [51].…”
Section: Simulation Of Fiber Fuse In Hafmentioning
confidence: 99%
“…Several researchers observed the dynamics of fiber fuse termination near a splice point between a HAF and an SMF by using a high-speed camera [42], [46], [48], [51].…”
Section: Simulation Of Fiber Fuse In Hafmentioning
confidence: 99%
See 1 more Smart Citation